Ageing by feet? Regional migration, neighbourhood choice and local demographic change in German cities - Uwe Neumann (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
In countries with an ageing population, regional migration may accentuate local progress in demographic change. This paper investigates whether and to what extent diversity in ageing among urban neighbourhoods in Germany was reinforced by regional migration during the past two decades. The old-industrialised Ruhr in North Rhine- Westphalia serves as a case study representing an advanced regional stage in ageing. The analysis proceeds in two steps. First, variation in the pace of neighbourhood-level demographic change over the period 1998-2008 is examined using KOSTAT, an annual time series compiled by municipal statistical offices. Second, a discrete choice model of household location preferences is applied to study the underlying demographic sorting process. The second step draws on microdata from a representative population survey carried out in 2010. During the 1990s and 2000s, in contrast to earlier decades, age differentials in location preferences became more profound and city centres became more popular as residential location. Rapid "ageing by feet" now affects neighbourhoods, where the influx is low, particularly low-density housing areas of the outer urban zone. Neighbourhood-level demographic sorting proceeds at a somewhat slower pace in the Ruhr than in the more prosperous cities of the nearby Rhineland (Bonn, Cologne and Dusseldorf). In the process of regional adaptation to demographic change, greater diversity in the age structure of neighbourhood populations may turn out to be an advantage in the long-run competition over mobile households. – – In Staaten mit alternder Bevölkerung kann sich der lokale Fortschritt des demografischen Wandels durch regionale Wanderungsbewegungen erheblich verstärken. Der Beitrag untersucht, ob und inwiefern die Diversität der demografischen Alterung auf der Ebene von Nachbarschaften in deutschen Städten in den vergangenen beiden Jahrzehnten durch regionale Migration beeinflusst wurde. Das Ruhrgebiet dient als Fallbeispiel einer im Alterungsprozess bereits fortgeschrittenen Region. Die Variabilität des Alterungsprozesses wird in zwei Stufen untersucht. In der ersten Stufe wird die Variation im Fortgang des demografischen Wandels auf der Ebene von Stadtteilen im Zeitraum von 1998 bis 2008 mit Hilfe des von kommunalstatistischen Ämtern zur Verfügung gestellten KOSTAT-Datensatzes untersucht. In der zweiten Stufe wird der zugrunde liegende demografische Segregationsprozess auf Basis eines Discrete-Choice-Modells der Wohnstandortpräferenzen von Haushalten untersucht. Die zweite Stufe greift auf Mikrodaten einer repräsentativen Haushaltsbefragung aus dem Jahr 2010 zurück. Während der 1990er und 2000er Jahre traten im Gegensatz zu früheren Jahrzehnten Altersunterschiede in den Standortpräferenzen deutlicher hervor und die Popularität der Stadtzentren als Wohnort nahm zu. Eine rasche 'Alterung mit den Füßen' betrifft Nachbarschaften, die keine starken Zuzüge verzeichnen, insbesondere die locker bebauten Wohngebiete der Ballungsrandzone. Die demografische Segregation zwischen Stadtteilen nimmt im Ruhrgebiet etwas langsamer zu als in den wirtschaftlich stärker prosperierenden Städten des benachbarten Rheinlands (Bonn, Düsseldorf, Köln). Im Verlauf der regionalen Anpassung an den demografischen Wandel könnte sich eine größere Vielfalt in der Altersstruktur der Wohnbevölkerung von Nachbarschaften als Vorteil im Wettbewerb um mobile Haushalte erweisen.
Keywords: C21; C25; O18; R23; 330; ageing; segregation; neighbourhood sorting; discrete choice